Pathogenic role of S100 proteins in psoriasis - Liang, Huifang; Li, Junqin; Zhang, Kaiming (Frontiers in Immunology, 2023)
Psoriasis is a chronic inflammatory skin disease. The histopathological features of psoriasis include excessive proliferation of keratinocytes and infiltration of immune cells. The S100 proteins are a group of EF-hand Ca2+-binding proteins, including S100A2, -A7, -A8/A9, -A12, -A15, which expression levels are markedly upregulated in psoriatic skin. These proteins exert numerous functions such as serving as intracellular Ca2+ sensors, transduction of Ca2+ signaling, response to extracellular stimuli, energy metabolism, and regulating cell proliferation and apoptosis. Evidence shows a crucial role of S100 proteins in the development and progress of inflammatory diseases, including psoriasis. S100 proteins can possibly be used as potential therapeutic target and diagnostic biomarkers. This review focuses on the pathogenic role of S100 proteins in psoriasis.